Implementation of Botanical Pesticides and Yellow Traps for Pest Control in Farmer Groups of Gombolirang Village, Kabat Sub-district, Banyuwangi Regency - Muhammad Dafa Riansyah; Nadia Dwi Safitri; Diah Ayuk Wulandari; Nazala Zaikumar Elfa Rizqi; Gita Puspita Sari; Ira Ika Puspitasari; Fiky Binti Zakiyah; Audina Rahma Sari; Fernanda Bagus Prasetya; Muhammad Doni Gunarso; Arif Mohammad Siddiq (Faculty of Mathematics and Natural Sciences, University of Jember, 2025)
The community service program conducted by the Community Service (KKN) Team of the University of Jember in Gombolirang Village provided practical solutions to agricultural challenges, particularly in pest and disease control. The program focused on introducing environmentally friendly alternatives, including the use of botanical pesticides made from easily accessible plant-based ingredients such as lemongrass, maja fruit, and garlic, as well as the installation of yellow traps. Activities carried out in August 2025 included field observation, farmer interviews, extension sessions, demonstrations on the production of botanical pesticides and yellow traps, along with interactive discussions with farmer groups from five hamlets (Krajan, Kertosari, Cungking, Sempu, and Ancar). Data were collected through direct observation and evaluation of the community’s response to the introduced innovations. The implementation of this program showed that farmers in Gombolirang Village were highly enthusiastic and successfully gained practical skills in producing botanical pesticides and applying yellow traps as cost-effective and environmentally friendly pest control methods. These technologies were considered effective in reducing pest populations without disrupting the rice field ecosystem. Most participants also expressed their willingness to independently apply these methods in the next planting season. Thus, this program contributed to enhancing farmers’ capacity and encouraging the adoption of sustainable agricultural practices at the local level.